Predictors of multiple injuries in individual distance runners: A retrospective study of 75,401 entrants in 4 annual races-SAFER XX - Sonja Swanevelder; Nicola Sewry; Martin Schwellnus; Esme Jordaan (Elsevier, 2022)
Background: There are limited data on factors that predict an increased risk of multiple injuries among distance runners. The objective of this study was to determine risk factors that are predictive of individual runners with a high annual multiple injury risk (MIR). Methods: A retrospective, cross-sectional study at 4 annual (2012-2015) Two Oceans 21.1 km and 56.0 km races in South Africa with 75,401 consenting race entrants. Running-related injury data were collected retrospectively through an online pre-race medical screening questionnaire. The average number of injuries for each runner every year was calculated by taking a runner's race entry history and injury history into account and categorizing entrants into 4 MIR categories (high, intermediate, low, and very low (reference)). Multiple logistic regression modeling (odds ratios) was used to determine whether the following factors were predictive of a high MIR (average > 1 injury/year): demographics, training and racing, chronic-disease history (composite chronic disease score (CCDS)), and history of allergies. Results: Of all entrants, 9.2% reported at least 1 injury, and 0.4% of entrants were in the high MIR category; the incidence rate was 2.5 injuries per 10 runner-years (95% confidence interval (95%CI): 2.4-2.7). Significant factors predictive of runners in the high MIR category were: running for > 20 years: OR = 2.0 (95%CI: 1.3-3.1; p = 0.0010); a higher CCDS: OR = 2.2 (95%CI: 2.0-2.4; p < 0.0001); and a history of allergies: OR = 2.8 (95%CI: 2.0-3.8; p < 0.0001). Conclusion: Runners who have been running recreationally for > 20 years and those with multiple chronic diseases or a history of allergies were at higher risk of multiple running-related injuries. This high-risk group can be targeted for further study and possible injury-prevention interventions.